Pengembangan Uji Eksperimental Penuaan Dipercepat Sistem Isolasi Kertas Terendam Minyak Transformator - Duanaputri, Rohmanita; Prasojo, Rahman Azis; Wiwaha, Sigit Setya; Akbar , Divac Nabiel; Handani, Galuh Prawestri Citra; Andrianto, Arif; Elyasa, Rizki Dias (Politeknik Negeri Malang, 2023)
A transformer is a static electric device that is used to change the alternating voltage to a higher or lower level and is used to transfer energy from one electric circuit to another without changing the frequency. When the transformer is working, there is a temperature rise in the transformer which affects the degradation of the insulating paper and transformer oil. This accelerated aging tester applies the drying and vacuuming process as well as the arrangement of paper insulation racks to achieve maximum test results. The research method refers to IEC 60216-3 2006 for aging time, IEC TS 62332-1 2014 and IEC TS 62332-1 2011 as a reference for the Development of Accelerated Aging Experimental Test Cells for Transformer Oil-immersed Paper Insulation Systems. After achieving the existing goals, the addition of the drying process resulted in quite good Breakdown Voltage test results, not only that after the addition of vacuum it produced a good oil color according to ASTM D1500 as well as after the presence of paper placement racks the results of good tensile strength testing were proven by a graph which relatively decreased from sample 1 to sample 3.